FACTORS THAT INFLUENCE IMPULSIVE BUYING BEHAVIOR AT TIKTOK LIVE STREAMING FASHION COMMERCE - Chintya Rembulan, Serafim
Nowadays, online users have largely adopted live streaming videos on TikTok. Due to its potential to capitalize on consumers' impulsive "see-now-buy-now" mentality, live streaming commerce has become an essential mainstream marketing channel for businesses. Few studies have looked into how consumers behave when making impulsive purchases but have overlooked the importance of real-time communication between buyers and sellers, the products involved in livestreaming commerce, and the platform itself. To bridge the knowledge gap, this research investigates the impact of customer’s perceived enjoyment and perceived usefulness on impulsive buying in live streaming commerce. This study collected primary data utilizing a quantitative approach by distributing Google Form survey to Bandung and Jakarta Metropolitan Area-based TikTok users between the ages of 16 and 26. The survey is distributed from June to July of 2023 through social media platforms. The research is analyzed by PLS-SEM. There are three factors which serve as a stimuli that impacts customers' affective perceptions (perceived enjoyment) which are the attractiveness, trustworthiness, and expertise of the seller. Other than that, there are three factors that impact customer's cognitive perceptions (perceived usefulness) which are product's usefulness, purchase convenience, and price promotion. These factors are related to the platform, which on this matter is TikTok fashion commerce. Ultimately, consumer's affective and cognitive perception of TikTok fashion commerce will influence their urge to buy impulsively. This research is expected to give insight for fashion brands to improve marketing strategies especially on emphasizing customers’ impulsive buying behavior.